LEGO® Block Structures as a Sub-Kelvin Thermal Insulator - Chawner, J. M. A. (Sci Rep, 2019)
We report measurements of the thermal conductance of a structure made from commercial Acrylonitrile Butadiene Styrene (ABS) modules, known as LEGO® blocks, in the temperature range from 70 mK to 1.8 K. A power law for the sample’s thermal conductivity κ = (8.7 ± 0.3) × 10(−5) T (1.75±0.02) WK(−1) m(−1) was determined. We conclude that this ABS/void compound material provides better thermal isolation than well-known bulk insulator materials in the explored temperature range, whilst maintaining solid support. LEGO blocks represent a cheap and superlative alternative to materials such as Macor or Vespel. In our setup, <400 nW of power can heat an experimental area of 5 cm(2) to over 1 K, without any significant change to the base temperature of the dilution refrigerator. This work suggests that custom-built modular materials with even better thermal performance could be readily and cheaply produced by 3D printing.